Determinación de la potencia antimicrobiana por el método Turbidimétrico. Antimicrobial potency assessment using the turbidimetric method. - Marmolejo- Ruíz , G.S.; Alba-Romero , J.J.; Rico-Del Rio , A.E.; Lozano-Morán , M.; Martínez-Romero , A.; Téllez-López , M.Á.; Hernández-González , S.I. (Revista de Ciencias Médicas Torreón, 2026)
The pharmaceutical industry is an essential sector within life science, facilitating the development of new drugs and technologies aimed at human and animal health. The quality of pharmaceutical products must be guaranteed through systematic evaluation processes that ensure both their efficacy and safety; in this context, the assessment of microbiological methods becomes an essential component within the quality control laboratory. The objective of this research was to determine the antimicrobial potency of an injectable pharmaceutical product with oxytetracycline as the active ingredient using the Turbidimetric method, as well as to design and validate the methodology. The methodology used refers to the general analysis method 0100, microbiological assay of antibiotics from the Mexican Pharmacopoeia. In this study, the antimicrobial potency obtained for the veterinary injectable pharmaceutical product with Oxytetracycline was 109.91%, which is acceptable. This result confirms that the drug inhibits the growth of the test microorganism, Staphylococcus aureus (ATCC 29373). By implementing this validated method, the reliability of the results is guaranteed.